2014
DOI: 10.4049/jimmunol.1302552
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 1γ1 Inhibits the RIG-I/TLR Signaling Pathway through Phosphorylating p65 and Promoting Its Degradation

Abstract: The casein kinase 1 (CK1) plays an important role in various biological processes by phosphorylating its target proteins. In this study, we demonstrate that CK1γ1 inhibits RNA virus–mediated activation of retinoic acid–inducible gene I (RIG-I) signaling by affecting the stability of NF-κB subunit p65. First, we found that ectopic expression of CK1γ1 inhibits RIG-I pathway–mediated activation of IFN-β, whereas knockdown of CK1γ1 potentiates the activation of IFN-β and NF-κB induced by Sendai virus (SeV). We the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…Our finding that Ser 534 phosphorylation enhanced p65 half-life in multiple cell types is consistent with two previous studies that also showed the increased half-life of S536A mutants (39, 40). Note that the effects of the S534A mutation were most substantial at later time points of stimulation (for example, 8 hours after LPS injection) in both the liver and spleen, which is consistent with the finding that Ser 536 phosphorylation reduces p65 half-life.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that Ser 534 phosphorylation enhanced p65 half-life in multiple cell types is consistent with two previous studies that also showed the increased half-life of S536A mutants (39, 40). Note that the effects of the S534A mutation were most substantial at later time points of stimulation (for example, 8 hours after LPS injection) in both the liver and spleen, which is consistent with the finding that Ser 536 phosphorylation reduces p65 half-life.…”
Section: Discussionsupporting
confidence: 93%
“…Note that the effects of the S534A mutation were most substantial at later time points of stimulation (for example, 8 hours after LPS injection) in both the liver and spleen, which is consistent with the finding that Ser 536 phosphorylation reduces p65 half-life. Previous studies demonstrated a role for the E3 ubiquitin ligases Cullin-based ligase 2 (CUL2) and Copper metabolism MURR1 domain–containing 1 (COMMD1) in the degradation of p65 in cultured cells in response to both Ser 468 and Ser 536 phosphorylation (40, 41). Because of the mild effect of S534A phenotype in the liver, the absence of effects at some time points, and the much lower effects in tissues such as the spleen, we could not determine to what degree these cofactors regulate p65 stability in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to study how Cdc25A balances its roles in cell cycle checkpoints and the antiviral immune response. We previously reported that CK1␥1 inhibits both RIG-I and TLR signaling by phosphorylating NF-B p65 and promoting its degradation (18). Because TBK1 is the common downstream component in RLRs/TLRs as well as DNA sensors, such as AIM2, cGAS, and DDX41-mediated signaling pathways (40), we postulate that Cdc25A may also inhibit TLR-and DNA sensor-mediated innate immune responses.…”
Section: Discussionmentioning
confidence: 88%
“…Because these responses are vital for eliminating invading pathogens, NF-B activity must be tightly regulated to avoid an excessive immune response, and many regulators have been reported to be involved in the process. For example, as a cytoplasmic LIM protein, PDLIM1 binds to and sequesters the NF-B subunit p65, thereby inhibiting NF-B-mediated inflammatory signaling (31), and casein kinase 1␥1 (CK1␥1) phosphorylates p65 and promotes its degradation to inhibit the RIG-I/TLR signaling pathway (32). Besides, RIG-I functions as a positive regulator of NF-B signaling by interacting with NF-B1 and enhancing its translation (6).…”
Section: Discussionmentioning
confidence: 99%